The probability of getting a loan: Evidence from Indian cities - Saon Ray; Smita Miglani; Sandeep Paul (Indian Council for Research on International Economic Relations (ICRIER), 2019)
Financial inclusion or access to financial services, is a major development goal for all nations across the globe. Financial inclusion does not concern only "access, but also the "use"" of financial services. This paper examines the loan taking behavior of individuals based on survey of 844 individuals across five cities in India. Probit regression has been used to ascertain the role of various socio-economic factors in affecting the loan taking behavior. The results indicate that the probability of taking a loan increases with the probability of owning a house and if a person is employed and has a bank account.
Keywords: D14; G20; G21; G41; O17; 330; Financial inclusion; household finance; financial literacy; India